ANALISIS USAHATANI CABE MERAH (Capsicum Annum L) DI DESA PEREAN TENGAH, KECAMATAN BATURITI, KABUPATEN TABANAN - I DEWA GEDE AGUNG; NI WAYAN PUTU ARTINI; NYOMAN RATNA DEWI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2000)
This research was carried out to study farmer’s income and profit gain fromfarm ordinary chili. The research is conducted at Perean Tengah village, Baturitidistrict, Tanbanan regency. Thirty farmers who done ordinary chili with monoculturesystem was taken randomly as samples.The result of the research show the average large farmbusiness was 0.14hectar with 1,670 kg products each farm (11,929 kg/hectar). While average revennewas Rp 13,999,610.00 each farm (Rp 99,997,214.00/hectar) with the chili price Rp8,383.00/kg. Meanwhile farmer expenditure for each farm was Rp 2,296,350.00 (Rp16,402,500.00/hectar), so farmer’s income and net profit were Rp 12,141,229.00 andRp 11,703,260.00 each farm respectively with Return-Cost-Ratio was 6.10, its meanthat the chili farmbusiness give much benefit to the farmers.